Disagreements in remembering, contradictions in commemoration. Main narrative trends in conflict of memories in Poland after 1989 - Ratke-Majewska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this article is to present how the concept of conflict of memories can be understood (referring to Poland after 1989), and to show what are the main directions of narratives in this conflict, formulated within the framework of several areas fundamental to Polish public discourse. It was also of great importance to discover what types of narratives construct each of the narrative trends about a particular past event. This made it possible to formulate conclusions concerning the shape of the featured conflict, its course and potential for permanence.
Keywords: conflict of memories; Poland after 1989; affirmative narratives; critical narratives; consensual narratives